Spiritual Loving and Mental Health: A Schelerian Perspective - Kobla Nyaku (Religions)
In this paper, I question what the relationship between psychology and spirit would mean for mental well-being if the ideas of the human being and the notion of spirit are viewed from the perspective of Max Scheler’s philosophical anthropology. Scheler provides a view of the human being and of spirit that differs radically from the generally held views, and his philosophical anthropology provides intellectual nourishment. This approach means that I do not look at spirituality as a religious activity or technique, but rather as a dimension of what constitutes the human being, and I explore how this view of spirituality is related to mental health. This paper is therefore divided into two parts. In the first part, I provide a summary of Scheler’s view of five ideologies of the human being in the history of Western philosophy that he identified, pointing out what he saw as their shortcomings. Next, I examine Scheler’s own philosophical anthropology that views the human being as the meeting place of the interpenetrating movements of spirit and impulsion, and as ens amans—a loving being. After that, I explore Scheler’s notion of spirit and personalism, drawing attention to the crucial role of what he describes as the dimension of spirit in his anthropology. In the second part of this paper, I explore the basic theories of well-being—hedonism, desire theories, and objective list theories—and question what a reading of spirituality as the participation in the movement of love would mean to addressing mental health. I conclude that spirituality should not be viewed as just another source of practices and techniques that could enhance human mental health. Rather, spirituality should be understood as a human being’s execution of the act that constitutes the core of his or her being. Spirituality viewed as the execution of the spiritual act of love—spirituality as loving being.